The Digitalisation of Swedish Housing - Fredrik Torisson (Footprint, 2023)
So called ‘smart’ built environments operate in a peculiar temporal nexus: they are simultaneously just around the corner, already here, and yesterday’s news. This is usually put down to hype and hyperbole, but it may well be argued that smart built environments do indeed exist across temporal dimensions – only not in the way we imagine them to.